Whole-genome combinatorial gene fusions generate novel genes for advanced microbial trait development - Melody M. McNay; Sabrina Baffert; Alan Greener; Christopher R. Schvarcz; B. Greg Mitchell; Helge Zieler (Proceedings of the National Academy of Sciences, 2026)
Translational fusion of two separate genes into a compound sequence encoding a fusion protein is a key evolutionary mechanism which underpins the emergence of new protein activities, families, and architectures. In biotechnology, gene fusion is a valuable molecular evolution tool for tagging proteins of interest and for combining or altering protein activities. To broadly demonstrate and harness the gain-of-function capabilities of fusion genes in a whole-genome approach, we constructed a “Function Generator™” fusion gene library containing pairwise combinations of 5,019 protein-coding sequences in the Saccharomyces cerevisiae genome. The open reading frames (ORFs) were PCR amplified from the S288C yeast genome and cloned into a centromeric expression vector, with each ORF represented in the 5′ and the 3′ positions of the resulting gene fusions. To illustrate the ability of fusion genes in the library to confer complex phenotypes, a population of yeast library transformants was screened for resistance to four toxic heavy metal ions (Cd +2 , Co +2 , Cu +2 , and Ni +2 ). Active fusion genes were cloned, validated, and sequenced, revealing a multitude of biological functions represented in these genes, including proteins involved in transcription, translation, metal ion binding and transport, and cell cycle control, as well as unknown functions. The gain-of-function principle of gene fusions was confirmed by comparing the activity of selected fusion genes to their constituent single ORFs expressed either individually or in nonfused pairs. Function Generator™ represents a powerful way to approach phenotypic diversity in the laboratory and to bypass a key evolutionary bottleneck for accelerated strain development.